Distribution and resource characteristics of the clam Anomalodiscus squamosus in Nha Phu waters, Khanh Hoa province - Ngai, Phan Duc; Nhung, Cao Thi Huyen (Vietnam Journal of Marine Science and Technology, 2019)
Distribution and resource characteristics of the clam Anomalodiscus squamosus in Nha Phu, Khanh Hoa province was studied by two surveys carried out in 2016–2017. The results have shown that, Anomalodiscus Squamosus was a good sources of income (804 tons/year and over 4.1 billion VND) for the communities living around the estuary of Nha Phu. Exploited yield of Anomalodiscus squamosus of dry season bigger than that in the rainy season (67% of total yield catches in both seasons). Anomalodiscus squamosus distributed in areas with temperature and salinity ranges from 29–31oC and 25–27‰, respectivelyand distributed along with other bivalves such as Gari elongata (Lamarck, 1818), Anadara nodifera (Martens, 1860), Anadara antiquata (Linnaeus, 1758) and were also affected by sandy sediments and mangroves, mainly sandy sediments. The results of this study provide a scientific basis for the proposed solutions for restoration, conservation and rational exploitation of Anomalodiscus squamosus.